2007
DOI: 10.1093/annonc/mdl500
|View full text |Cite
|
Sign up to set email alerts
|

Change in CA 125 levels after the first cycle of induction chemotherapy is an independent predictor of epithelial ovarian tumour outcome

Abstract: Among well-established prognostic factors in ovarian cancers, the CA 125 change after first course of CT was independent prognostic factors for both achievement of pathological complete response and OS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 13 publications
0
18
0
2
Order By: Relevance
“…This tumor marker has proven to be an important parameter in the differential diagnosis of EOC and particularly in monitoring the response to treatment and recurrence of tumor. 16,17 Preoperative CA125 has been proven to be a reliable predictor for optimal cytoreduction, and the best cutoff value for this prediction is 500 IU/mL. 18,19 Therefore, we adopted 500 IU/mL as the threshold.…”
Section: Discussionmentioning
confidence: 99%
“…This tumor marker has proven to be an important parameter in the differential diagnosis of EOC and particularly in monitoring the response to treatment and recurrence of tumor. 16,17 Preoperative CA125 has been proven to be a reliable predictor for optimal cytoreduction, and the best cutoff value for this prediction is 500 IU/mL. 18,19 Therefore, we adopted 500 IU/mL as the threshold.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that longitudinal measurements contain valuable information that cannot be fully represented by examining a single value or a kinetic factor. In addition, studies that considered CA-125 over a period of time treated multiple CA-125 levels individually [20,25,26], and there is so far no report that has taken all the measurements and fitted them concurrently to a survival model.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, regulatory authorities accept RECIST as the gold standard for such assessments [11]. Some studies have reported that the relationship of serial tumor marker monitoring with tumor response and survival in germ cell tumors [18][19][20], pancreatic carcinoma [21], ovarian tumor [22], prostate cancer [23].…”
Section: Discussionmentioning
confidence: 99%